2004
DOI: 10.1007/s00015-004-1114-9
|View full text |Cite
|
Sign up to set email alerts
|

Late Neogene extension in the vicinity of the Simplon fault zone (central Alps, Switzerland)

Abstract: Brittle faults and kinematic indicators have been measured systematically below and above the major late alpine extensional Simplon fault in the vicinity of Simplonpass. Paleo-stress inversion has been conducted for a total of over 1200 fault measurements, from 62 sites. Minor faults in both hanging-and footwall of the Simplon fault define a coherent paleo-stress field with SW-NE oriented maximum horizontal extension and near vertical compression. The kinematics of these latest brittle deformations are in very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
(34 reference statements)
0
32
0
Order By: Relevance
“…Figure 13 presents examples of such normal faults, and related meso-scale and large-scale structures. Numerous other examples of such extensional and transcurrent late Alpine structures have been published in the Western and Central Alps (e.g., Tricart 2002, 2003;Champagnac et al 2003Champagnac et al , 2004Grosjean et al 2004). At first sight, the overall pattern of the r3 axes (Fig.…”
Section: Orogen-parallel Versus Orogen-perpendicular Extensionmentioning
confidence: 88%
See 1 more Smart Citation
“…Figure 13 presents examples of such normal faults, and related meso-scale and large-scale structures. Numerous other examples of such extensional and transcurrent late Alpine structures have been published in the Western and Central Alps (e.g., Tricart 2002, 2003;Champagnac et al 2003Champagnac et al , 2004Grosjean et al 2004). At first sight, the overall pattern of the r3 axes (Fig.…”
Section: Orogen-parallel Versus Orogen-perpendicular Extensionmentioning
confidence: 88%
“…Regardless of this somewhat semantic issue, we deal with the reconstruction of the stress state acting within the belt since Early Miocene times. A series of regional analyses has been incorporated into our large-scale synthesis (Champagnac et al 2003Grosjean et al 2004). This provides a large and rather homogenous database (312 paleostress tensors) covering the entire arc of the inner Western and Central Alps, corresponding to a surface of some 10,000 km 2 (average density of 3 tensors/100 km 2 ).…”
Section: Orogen-parallel Versus Orogen-perpendicular Extensionmentioning
confidence: 99%
“…In its central section, it is marked by a zone of foliated clay gouge that can be up to a few meters wide. Kinematic indicators from both the ductile and brittle components consistently show a top down to the SW shear sense [Mancktelow, 1985[Mancktelow, , 1987[Mancktelow, , 1990Grosjean et al, 2004]. In contrast, older structures are generally well preserved in the hanging wall, showing overprinting relationships between several deformation phases that correspond well in their orientation and style to the four regional phases, D1 to D4 [Milnes et al, 1981].…”
Section: Simplon Fault Zonementioning
confidence: 99%
“…Grosjean et al 2004;Champagnac et al 2004). These studies have shown that, south of the Rhone Valley, a first phase of orogen-parallel (NE-SW) extension, including normal faulting along the Simplon fault and dextral strike-slip faulting along the Rhone fault, was succeeded by a second phase of orogenperpendicular (NW-SE) extension, the latter also recorded by the present-day stress field (Maurer et al 1997;Delacou et al 2004).…”
Section: Discussionmentioning
confidence: 99%